2018
DOI: 10.1159/000487545
|View full text |Cite
|
Sign up to set email alerts
|

LVIS Jr Device for Y-Stent-Assisted Coil Embolization of Wide-Neck Intracranial Aneurysms: A Multicenter Experience

Abstract: Background and Purpose: Complex wide-neck intracranial aneurysms are challenging to treat. We report a multicenter experience using the LVIS Jr stent for “Y-stent”-assisted coiling embolization of wide-neck bifurcation aneurysms. Methods: Seven centers provided retrospective data on patients who underwent Y-stenting. Technical complications, immediate posttreatment angiographic results, clinical outcomes, and imaging follow-up were assessed. Results: Thirty patients/aneurysms were treated: 15 basilar tip, 8 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 37 publications
5
23
0
Order By: Relevance
“…At a mean follow-up of 5.2 months, 23 patients out of 26 (96%) had complete occlusion. This study supports the use of Y-stenting with the LVIS Jr device to assist in endovascular coiling of bifurcated, wide-neck cerebral aneurysms 27…”
Section: Advances In Stent-assisted Coilingsupporting
confidence: 74%
“…At a mean follow-up of 5.2 months, 23 patients out of 26 (96%) had complete occlusion. This study supports the use of Y-stenting with the LVIS Jr device to assist in endovascular coiling of bifurcated, wide-neck cerebral aneurysms 27…”
Section: Advances In Stent-assisted Coilingsupporting
confidence: 74%
“…For example, a recent LVIS stent (MicroVention, Aliso Viejo, California, USA) HDE study of 31 patients reported a technical success rate of 93.1% with ≥90% occlusion rate of 92.9% and complete occlusion rate of 75% at 6 months angiography, with 0% morbidity and mortality 8. Another 30 patient multicenter retrospective study using the braided LVIS Jr microstent demonstrated 3.3% morbidity rate with no mortality and complete occlusion rate of 76% (21/25) Raymond class I on a mean follow-up of 5.2 months, with one patient reporting permanent complications (3.3%) 9. The Canadian LVIS Jr multicenter registry of 102 patients demonstrated a complete long-term occlusion rate (defined as Raymond class I) of 68%, with 3% permanent neurological deficits, and 1% overall mortality rate 10…”
Section: Discussionmentioning
confidence: 98%
“…Both LVIS Jr and Neuroform Atlas stents provide low profile advantages with delivery through a 0.017-inch microcatheter. Several centres have published procedural successes with both VRDs in Y-stent assisted coilings for wide-necked aneurysms 30–32. In comparison with the tubular constructs of LVIS Jr and Neuroform Atlas VRDs, the PulseRider stent was uniquely designed in two distinct shapes, T or Y, with the intention to address coiling challenges of wide-necked bifurcation aneurysms.…”
Section: Treatment Optionsmentioning
confidence: 99%